2022
DOI: 10.3389/fpsyg.2022.882394
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Holistic Communication Approach to an Automated Vehicle's Communication With Pedestrians: Combining Vehicle Kinematics With External Human-Machine Interfaces for Differently Sized Automated Vehicles

Abstract: Future automated vehicles (AVs) of different sizes will share the same space with other road users, e. g., pedestrians. For a safe interaction, successful communication needs to be ensured, in particular, with vulnerable road users, such as pedestrians. Two possible communication means exist for AVs: vehicle kinematics for implicit communication and external human-machine interfaces (eHMIs) for explicit communication. However, the exact interplay is not sufficiently studied yet for pedestrians' interactions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Most previous studies observed that front signal light only convey implicit signals when vehicles slow down 30 . In reality, however, many drivers do not slow down in front of zebra crossings under unsignalized roadways or even pass at a constant speed or accelerate to indicate that they are not yielding.…”
Section: Implicit and Explicit Signalsmentioning
confidence: 97%
See 1 more Smart Citation
“…Most previous studies observed that front signal light only convey implicit signals when vehicles slow down 30 . In reality, however, many drivers do not slow down in front of zebra crossings under unsignalized roadways or even pass at a constant speed or accelerate to indicate that they are not yielding.…”
Section: Implicit and Explicit Signalsmentioning
confidence: 97%
“…The results showed that the overall communication effect had great potential when the signal expression of the eHMI was aligned with the vehicle’s kinematic state. However, the findings also highlighted that when the signaling of the eHMI contradicted the behavior of the vehicle, the consequences could be fatal 30 . Moreover, when a vehicle has an eHMI, humans may ignore the actual movement state of the vehicle and focus instead on the signals presented by the eHMI 29 .…”
Section: Implicit and Explicit Signalsmentioning
confidence: 98%
“…Werner et al [71] identified turquoise as the best color for AV external lighting, emphasizing visibility and uniqueness. Lau et al [40] showed that dynamic eHMI enhances safety in yielding AVs but warned against mismatches between eHMI signals and vehicle actions. Dey et al [18] discovered cyan with flashing or pulsing animations as effective for eHMIs in AVs, aiding pedestrian interaction.…”
Section: Related Work 21 Autonomous Vehicles-pedestrian Interaction D...mentioning
confidence: 99%
“…References: [22,[33][34][35]. Rationale: The communication of the CAV must be consistent and shall not send any contradicting messages to avoid a feeling of uncertainty.…”
Section: Principle A3: Prosocial Communicationmentioning
confidence: 99%
“…References: [6,17,18,22,[36][37][38][39][40]. Rationale: According to §1 of the German Road Traffic Act (StVO), all road users should behave in such a way that no one is endangered, harmed, hindered, or disturbed.…”
Section: Principle A3: Prosocial Communicationmentioning
confidence: 99%